Characteristic and Mechanism of Drug-Herb Interaction Between Acetylsalicylic Acid and Danhong Injection Mediated by Organic Anion Transporters - Li, Jianping; Lu, Jingbo; Peng, Yin; Xu, Xuejun; Chen, Chenkai; Gao, Ming; Lin, Ling; Guo, Jianming; Duan, Jinao (Frontiers in Pharmacology, 2020)
The mixture of Salvia miltiorrhiza and Carthamus tinctorius (Danhong injection, DHI) is widely prescribed in China for the treatment of cardiovascular and cerebrovascular diseases. In most cases, DHI is used in combination with acetylsalicylic acid (ASA). However, the interaction between DHI and ASA remains largely undefined. The purpose of this study is to explore the interaction profile and mechanism between DHI and ASA. The frequency of drug combination of DHI and ASA was analyzed based on 5183 clinical cases. The interaction characteristics were evaluated by analyzing the pharmacokinetics and disposition profile of salicylic acid (SA, the primary metabolite of ASA) in rats. The interaction mechanisms were explored through evaluating the hydrolysis of ASA regulated by ASA esterase, the tubular secretion of SA mediated by influx and efflux transporters, and the tubular reabsorption of SA regulated by urinary acidity-alkalinity. The inhibitory potential of DHI on organic anion transporters (OATs) was further verified in aristolochic acid I (AAI) induced nephropathy. Clinical cases analysis showed that DHI and ASA were used in combination with high frequency of 70.73%. In drug combination of DHI and ASA, the maximum plasma concentration of SA was significantly increased by 1.37 times, while the renal excretion of SA was significantly decreased by 32.54%. The mechanism study showed that DHI significantly inhibited the transport function, gene transcription and protein expression of OATs. In OATs mediated AAI nephropathy, DHI significantly reduced the renal accumulation of AAI by 55.27%, and alleviated renal damage such as glomerulus swelling, tubular blockage and lymphocyte filtration. In drug combination of DHI and ASA, DHI increased the plasma concentration of SA not through enhancing the hydrolysis of ASA, and the tubular reabsorption of SA was not significantly affected. Inhibition of tubular secretion of SA mediated by OATs might be the reason that contribute to the decrease of SA renal excretion.